2015
DOI: 10.1002/cbic.201500439
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Zwitterionic Polymer Conjugates of a Protein Have Long Plasma Circulation

Abstract: Many proteins suffer from sub-optimal pharmacokinetics (PK) that limit their utility as drugs. The efficient synthesis of polymer conjugates of protein drugs with tunable PK to optimize their in vivo efficacy is hence critical. We report here the first study of the in vivo behavior of a site-specific conjugate of a zwitterionic polymer and a protein. To synthesize the conjugate, we first installed an initiator for atom transfer radical polymerization (ATRP) at the N-terminus of myoglobin (Mb-N-Br). Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…179 Uricase is a therapeutic protein for the treatment of chronic gout. 182 The PCB-protein conjugates exhibited the enhanced serum half-life in vivo. 180 Recently, it was reported that PCB-conjugation to enzymes led to exceptional thermal stability and enhanced substrate-binding affinity, while PEGylation slightly increased the thermal stability with a significantly reduced affinity.…”
Section: Zwitterionic Polymersmentioning
confidence: 98%
See 1 more Smart Citation
“…179 Uricase is a therapeutic protein for the treatment of chronic gout. 182 The PCB-protein conjugates exhibited the enhanced serum half-life in vivo. 180 Recently, it was reported that PCB-conjugation to enzymes led to exceptional thermal stability and enhanced substrate-binding affinity, while PEGylation slightly increased the thermal stability with a significantly reduced affinity.…”
Section: Zwitterionic Polymersmentioning
confidence: 98%
“…Uricases, encapsulated in PCB hydrogels, showed a much higher thermal stability and better pharmacokinetic values, but did not induce the generation of antibodies in contrast to PEGylated uricase. 182 181 The enhanced binding affinity of PCB conjugation was attributed to the superhydrophilicity of PCB causing the removal of water from the active site of the enzyme.…”
Section: Zwitterionic Polymersmentioning
confidence: 99%
“…As an example, MALLS when coupled with size exclusion chromatography provides information on conjugate molar mass and radius of gyration ( R g ) while dynamic light scattering (DLS) data provides information on hydrodynamic radius ( R h ). When combining MALLS and DLS data, the conformation of the attached polymer around the protein can be determined by calculating the R g /R h shape ratio . This is extremely useful characterization technique for determining structure‐function‐dynamic relationships because one can determine if the polymer is wrapped tightly around the protein surface or fully extended into the surrounding solution.…”
Section: Characterize: Pitfalls and Future Needsmentioning
confidence: 99%
“…PEGylation is performed to improve pharmacokinetics and reduce immunogenicity by altering the physiochemical properties of the biomolecule by coating it with polymer. The increasing knowledge of the functions of protein‐polymer conjugates, new chemistries to create bioconjugates, and broadened range of polymer types, including “smart materials,” enabled multiple potential applications of protein‐polymer conjugates in medicine including drug delivery, sensing/detection, and incorporation into complex matrices …”
Section: Utilize: Applications Of Protein‐polymer Conjugatesmentioning
confidence: 99%
“…1113 This has been shown to increase NP clearance by macrophages of the RES, and decrease their downstream therapeutics. 1417 The RES, an arm of the immune system consisting of phagocytic cells, can prevent the site-specific accumulation of NPs that is important for NP diagnostics and therapeutics. 1821 Because of these undesirable effects, NP surfaces are typically neutralized.…”
Section: Introductionmentioning
confidence: 99%